A second species, and first Central American record, of the phorid fly genus Lenkoa Borgmeier (Diptera: Phoridae) - Brown, Brian V.; Porras, Wendy (Zootaxa, 2016)
A second species, and first Central American record, of the phorid fly genus Lenkoa Borgmeier (Diptera: Phoridae).        Many species of phorid flies have wingless or brachypterous females. Mostly, they belong to a group classified within the subfamily Metopininae corresponding to the Metopina group of genera of Brown (1992a) or the tribe Metopinini of Disney (2003, not 1987). The males of this group are much more typical in appearance, with well-developed wings, larger eyes, and fully developed abdominal tergites. These males carry females during a mating flight, often dispersing them to new breeding sites (Miller 1984). Generally, the sexual dimorphism is so great that the sexes cannot be confidently associated unless they are collected in copula. This has led to a profusion of species being described as males and females in separate genera. Some of these brachypterous females, both within the Metopinini and elsewhere in other Phoridae, have been correctly associated with their males when they are found together (e.g., Brown 1986, 1992b, 1994), but many remain unassociated.